2023
DOI: 10.1108/ajems-10-2022-0418
|View full text |Cite
|
Sign up to set email alerts
|

Non-linearity in the Phillips curve: evidence from Nigeria

Olufemi Gbenga Onatunji,
Oluwayemisi Kadijat Adeleke,
Akintoye Victor Adejumo

Abstract: PurposeThis study reinvestigates the validity of the Phillips curve in Nigeria for the period 1980–2020 by considering the asymmetric nexus between unemployment and inflation.Design/methodology/approachThe nonlinear autoregressive distributed lag (NARDL) technique was used to decompose the unemployment variable into two components: tight and loosened labour markets.FindingsThe empirical outcome shows that unemployment has a significant negative effect on inflation when the labour market is tight and a weakly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…This finding validates Phillip's (1958) theoretical argument that inflation increases steeply when unemployment is low, and the change in inflation becomes flat at a high unemployment rate. This outcome is congruent with the findings of Kumar and Orrenius (2015), Nalewaik (2016), Albuquerque and Baumann (2017), Bryne and Zekaite (2017), Bishop andGreenland (2021), andOnatunji et al (2023), who discovered similar findings in their investigations. Additionally, the results show that positive (rising) unemployment has a significant negative effect on inflation, while negative (declining) unemployment has an insignificant negative impact on inflation in Cape Verde, Gambia, and Guinea-Bissau.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This finding validates Phillip's (1958) theoretical argument that inflation increases steeply when unemployment is low, and the change in inflation becomes flat at a high unemployment rate. This outcome is congruent with the findings of Kumar and Orrenius (2015), Nalewaik (2016), Albuquerque and Baumann (2017), Bryne and Zekaite (2017), Bishop andGreenland (2021), andOnatunji et al (2023), who discovered similar findings in their investigations. Additionally, the results show that positive (rising) unemployment has a significant negative effect on inflation, while negative (declining) unemployment has an insignificant negative impact on inflation in Cape Verde, Gambia, and Guinea-Bissau.…”
Section: Resultssupporting
confidence: 92%
“…The empirical outcomes indicated that, at a specific threshold, the relationship between the variables weakens during periods of rising unemployment but becomes stronger as the labour market strengthens. Similarly, Onatunji et al (2023) investigated the asymmetric Phillips curve in Nigeria spanning 1980-2020 using the non-linear ARDL procedure. The authors discovered that declining unemployment spurs rising inflation, while increasing unemployment leads to low inflation in the country.…”
Section: Brief Literature Reviewmentioning
confidence: 99%